Penapisan Fitokimia, Fitur Antioksidan, dan Uji Toksisitas pada Ekstrak Metanol Kubis Ungu (Brassica oleracea var. capitata L.) - Alvionica, Selina; Hendrawan, Siufui; Ferdinal, Frans (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to analyze the phytochemical content, antioxidant properties and toxicity of methanolic extract of red cabbage originating from West Java, Indonesia. The study comprised in vitro assays, which included phytochemical screening, determination of total phenolic level, and antioxidant activity tests. The toxicity was tested using Brine Shrimp Lethality Test (BSLT). The screening results revealed the presence of various secondary metabolites in the extract. The total phenolic content of red cabbage was 29.8 mgGAE/g. The antioxidant potential was evaluated through the FRAP (Ferric Reducing Antioxidant Power) and ABTS (2,2'-Azino-bis(3-ethylbenzothiazoline-6-sulfonic acid)) assays, yielding IC50 values of 13.42 µg/mL and 21.28 µg/mL, respectively; both were classified as having a strong antioxidant activity. The BSLT toxicity test showed an LC50 value of 153.87 µg/mL. These findings suggest that red cabbage is rich in beneficial phytochemicals and acts a strong natural antioxidants source. Moreover, it demonstrates potential for future development as a standardized herbal medicine with antioxidant properties and an affordable price.